2002
DOI: 10.1351/pac200274081383
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis project. A new yellow carotenoid

Abstract: Naturally occurring colorants have been used in food processing for centuries to give meals an appealing color. In the first half of the 20 th century, the newly discovered brilliant azo dyes, amongst other artificial colorants (indol, triphenylmethane, and methine dyes), were used as pigments for food coloration. The toxicity and/or allergenic potential of some of these colorants were discovered much later. One of these pigments with a critical safety profile is the azo dye tartrazine, which exhibits a nicely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
2
9
2
1
Order By: Relevance
“…Conversely, there were no significant differences in the content of 9‐ cis ‐violaxanthin‐neoxanthin in the treated FW‐SM beverage at the end of the storage regarding its initial values. Different to our results, it has been reported that there was a sharp decrease in the 9‐ cis ‐violaxanthin‐neoxanthin content in an untreated and HIPEF‐treated orange juice and an orange‐carrot juice stored at 10C, and it was not detected in the beverages after sixth and three weeks, respectively (Giger ; Cortés et al . ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, there were no significant differences in the content of 9‐ cis ‐violaxanthin‐neoxanthin in the treated FW‐SM beverage at the end of the storage regarding its initial values. Different to our results, it has been reported that there was a sharp decrease in the 9‐ cis ‐violaxanthin‐neoxanthin content in an untreated and HIPEF‐treated orange juice and an orange‐carrot juice stored at 10C, and it was not detected in the beverages after sixth and three weeks, respectively (Giger ; Cortés et al . ).…”
Section: Resultscontrasting
confidence: 99%
“…Conversely, there were no significant differences in the content of 9-cis-violaxanthinneoxanthin in the treated FW-SM beverage at the end of the storage regarding its initial values. Different to our results, it has been reported that there was a sharp decrease in the 9cis-violaxanthin-neoxanthin content in an untreated and HIPEF-treated orange juice and an orange-carrot juice stored at 10C, and it was not detected in the beverages after sixth and three weeks, respectively (Giger 2002;Cort es et al 2006). Since carotenoids are dissolved in fat matrix, where they are protected from oxidizing action by vitamin E and other antioxidants (Ball 1988), it may be possible that the fat content of the whole milk used as ingredient of the FJ-WM beverages acted as a protector of this carotenoid from degradation or, inclusive leads to other reactions that induce to its formation.…”
Section: Effects Of Storage On Carotenoid Profilecontrasting
confidence: 99%
“…High pigment content, leading to a dark color or black material, absorbs more light. As a result, the absorbance peak is higher, in accordance with [1] β-carotene that exhibits in hexane a λ max of 452 nm. Solvents play a major role in the process of extracting the pigments.…”
Section: Resultssupporting
confidence: 59%
“…If critical consumers do not perceive a substantial benefit from an added ingredient (e.g., an enhanced stability by the addition of antioxidants), they might not buy the products [1]. Indonesian food produces in this field still do not control the use of food additives.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of E102 is now banned in several countries and restricted in others owing to its unfavorable safety profile. 16 E102 can be subject to reductive enzymatic cleavage of the azo group that leads to sulfonated aromatic amines, which exhibit little toxicological risk. It can be considered that this dye presents little risk owing to its high molecular weight, which does not allow penetration through the membranes of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%